HANDLING OF PROBLEM WORKING CAPITAL FINANCING IN INDONESIAN SHARIA BANK (BSI) - Desy Safitri; Syarifa Yusni Putri; Maulisa Arianti; Muhammad Alfarid; Jeri Saputra; Aidil Pahmi; Muhammad Aqshal Wiranata; Muhammad Dicky Suandy; Tri Wina Handani (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Working capital financing is an important part of the Company's operations. For Islamic banks, working capital is one of the most important products offered to customers. However, in practice, there are cases of problematic working capital financing that can affect the financial stability of Islamic banks in Indonesia. The results of the study show that several factors cause problematic working capital financing at Bank Syariah Indonesia, including: the inability of debtors to fulfill their payment obligations, poor bank management in controlling the use of funds and high business risks in several sectors. Several possible strategies include tightening control and supervision of the use of financial assets, improving credit processes, diversifying the financial portfolio and strengthening risk management. cooperation between Islamic banks and external parties such as economic monitoring institutions and consulting service companies can help overcome problematic working capital financing. All these efforts must be supported by proper regulations and the development of qualified human resources in the field of Islamic finance. This study is expected to provide a better understanding of the problems of working capital financing at Bank Syariah Indonesia and provide recommendations to banks and regulators to improve the management of these problems.